Doprinos različitih komponenata fonološke svesnosti ranom čitanju - Čolić, Gordana; Savić, Maja (Specijalna edukacija i rehabilitacija, 2025)
Introduction. Phonological awareness has proved to be one of the fundamental skills underlying the development and acquisition of reading ability in various languages, including those with transparent orthography such as Serbian. In this context, it is assumed that insufficiently developed phonological awareness limits the development of reading skills. Objective. The aim of this study is to examine the relationship between different components of phonological awareness and early reading in typically developing children. Method. The sample included 91 children who were tested twice: first during the preschool period, when various components of phonological awareness were assessed (12 tasks), and second at the end of the first grade, when reading (speed, accuracy, and comprehension) was assessed. Results. The results of the canonical correlation analysis showed the existence of three significant functions that connect phonological awareness in the preschool period with reading skills in the first grade: the first function links developed basic phonological skills (synthesis and segmentation of syllables and phonemes, sensitivity to rhyme) with accurate reading; the second function shows a relationship between more complex phonological skills such as phoneme manipulation, word segmentation, and rhyme production with better reading comprehension and faster reading; while the third function indicates a connection between phoneme manipulation skills and both reading speed and accuracy. Conclusion. The findings of this study point to the need to create and apply programs that support the development of specific components of phonological awareness before formal reading instruction, in order to improve the acquisition of various aspects of reading and to prevent reading difficulties.
Keywords: phonological awareness; phonemic awareness; early reading; transparent orthography; practical implications